Cattle’s Physiology and Behavior Responses Which Transported by Camara Nusantara Vessel - Shabrina Dyah Wibawanti; Mohammad Yamin; Rudi Afnan; Rudy Priyanto (Faculty of Animal Science, Jenderal Soedirman University in associate with the Animal Scientist Society of Indonesia (ISPI) and the Indonesian Association of Nutrition and Feed Science (AINI), 2021)
This study aimed to assess the welfare and performance of Bali cattle transported by Camara Nusantara vessel. We observed five-day transporting of 30 Bali cattle (1-2 years old, 100-200kg body weight) from cattle loading at Tenau Port, Kupang and cattle handling during sea transportation to cattle unloading at Tanjung Priok Port, Jakarta. The measured parameters were cattle’s physiological responses, including body surface temperature, foaming (excessive foam around their mouth), respiration (respiration rate during transportation), and panting (any panting behavior during the transport). The behavioral responses measured in this study were feeding behavior (do cattle eat normally during transportation process), lying (can cattle lie normally), agonistic interaction (mounting, head fighting, etc.), freeze during the loading/ unloading process (stop walking during loading and unloading process), coercion (cattle was hit during loading and unloading process), and slip/fall (cattle slipped or fell during loading and unloading process). The welfare evaluation was carried out by scoring system on the observed parameters. The result showed that the cattle showed a normal physiological response, except their body surface temperature was slightly above normal, i.e., 32-35oC. The cattle also showed normal behavior responses except for coercion. The average score gets from this study was 2.5, indicative of slightly poor physiology and behavior when cattle being transported.